Hyperoxidized Albumin Modulates Platelets and Promotes Inflammation Through CD36 Receptor in Severe Alcoholic Hepatitis. Issue 1 (23rd November 2019) - Bhat, Adil; Das, Sukanta; Yadav, Gaurav; Chaudhary, Sudrishti; Vyas, Ashish; Islam, Mojahidul; Gupta, Abhishak C.; Bajpai, Meenu; Maiwall, Rakhi; Maras, Jaswinder Singh; Sarin, Shiv K.
Abstract : Hyperoxidized albumin promotes inflammation and modulates several immune cells in severe alcoholic hepatitis (SAH). Platelets mediate inflammation by interacting with immune cells, endothelium, and other cells. The role of hyperoxidized albumin in platelet activation and alteration of platelet phenotype/functions is not known. Quantitative platelet proteomics performed in 10 patients with SAH was compared with 10 patients with alcoholic cirrhosis and 10 healthy controls, respectively. Dysregulated pathways were identified and validated in a separate cohort (n = 40). Healthy platelets were exposed to patient plasma or purified albumin or ex vivo modified albumin (human‐mercaptalbumin, humannonmercaptalbumin‐1, and human nonmercaptalbumin 2 ) in the presence or absence of CD36 blockade, and platelet secretome was analyzed. Two hundred and two up‐regulated proteins linked to platelet activation, complement regulation, lipid transportation, and 321 down‐regulated proteins related to platelet hemostasis and coagulation (fold change ± 1.5, P  < 0.01) were identified. Blood transcription module enrichment showed an inflammatory phenotype of SAH platelet. Increased level of platelet factor‐4, P‐selectin, and soluble cluster of differentiation‐40 ligand correlated with severity (Model for End‐Stage Liver Disease score, r > 0.3, P  < 0.05) in SAH. Transcripts linked to platelet activation (increased) and granular secretions (decreased in SAH) correlated with disease severity. SNARE (soluble‐N‐ethylmaleimide‐sensitive‐factor‐activating‐protein‐receptor) complex proteins (SNAP‐23 [synaptosomal‐associated protein 23] and VAMP‐8 [vesicle‐associated membrane protein 3]) were down‐regulated in SAH platelets ( P  < 0.05). In vitro stimulation of healthy platelets showed enhanced activation with patient plasma, or purified albumin‐treatment blocking of CD36 blunted this effect ( P  < 0.05). Ex vivo modified albumin (primarily nonmercaptalbumin–human nonmercaptalbumin 2 [HNA2; 1 mg/mL]) showed high activation and aggregation and intracellular reactive oxygen species production in healthy platelets ( P  < 0.05), which significantly reduced after CD36 neutralization. Platelet secretome showed reduced inflammatory mediators and increased repair proteins. Conclusion: Hyperoxidized albumin triggers platelet activation (possibly through the CD36 receptor), promotes inflammation and oxidative stress, and contributes to disease severity in patients with SAH. Abstract : Hyperoxidized albumin activates immune cells; however, its contribution in activation of platelets and change in proteome, which correlates with outcomes in SAH, is unknown. Platelets of patients with SAH are hyperactivated, facilitate oxidative stress and systemic inflammation, and have dysregulated granule secretion due to alteration in the expression of SNARE proteins. Oxidized albumin human nonmercaptoalbumin‐2 (HNA2) causes platelet activation and promotes inflammation and oxidative stress through the CD36 receptor–mediated redox pathway. Neutralization or blockade of platelet CD36 receptor and/or removal of HNA2 could serve as an attractive therapeutic strategy for reducing systemic inflammation and oxidative stress in patients with SAH.